PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP LITERASI SAINS DAN PEMAHAMAN KONSEP SISWA KELAS V SDN MEKARMUKTI 02 - Ainun Naim; Awalina Barokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the influence of the Problem Based Learning (PBL) problem based learning model on science literacy and conceptual understanding of grade V students at SDN Mekarmukti 02. In the context of 21st century education, it is important to equip students with critical thinking and problem-solving skills. Strong science literacy is an important benchmark, especially considering Indonesia's low ranking in the 2018 PISA results. This study uses a quantitative method with a nonequivalent control group experimental design. The research participants were grade V students of SDN Mekarmukti 02. Data were collected through questionnaires before and after the implementation of PBL. Data analysis shows that PBL has a significant influence on improving students' science literacy and understanding of concepts. PBL helps students relate learning to real-life experiences and improve critical thinking skills. This study recommends further development and training for teachers to optimize the implementation of PBL in the classroom.